Impact of dual sensory impairment on the risk of incident dementia: a protocol for a systematic review and meta-analysis - Giannoni-Luza, Stefano; Urso, Daniele; Alaoui, Ahmed Amine; Ting, Jeremy; Jabbour, Samir; Fuente, Adrian (BMJ open, 2024)
IntroductionStrong evidence supports the importance of potentially modifiable risk factors for dementia, with sensory loss, particularly visual and hearing impairment, being prominent among them. While single sensory impairment has been widely investigated, the influence of concomitant visual and hearing impairment is still not clear. Thus, in this systematic review, we aim to evaluate the risk of developing all-cause dementia due to dual sensory (visual and hearing) impairment and to comprehensively explore possible sources of heterogeneity.Methods and analysisThis protocol follows the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols 2015 statement and has been registered on the PROSPERO international prospective register of systematic reviews. Our literature search will include two databases: MEDLINE-PubMed and Embase. The search strategy will consist of terms tailored for each database. We will include peer-reviewed longitudinal cohort studies reporting HRs. Screening and selection of articles will be performed independently by at least two reviewers using the Covidence systematic review manager. Discrepancies will be resolved by consensus. Data will be collected on study design, location, study setting, follow-up years, baseline demographics, sensory impairment and dementia diagnosis ascertainment, and number of adjusted covariates. The quality of the included studies will be evaluated using the Newcastle-Ottawa Scale for cohort studies. If meta-analysis is possible, we will perform DerSimonian-Laird random-effects models of HRs using the most adjusted model from each study. Subgroup analyses and meta-regressions are planned as a function of study setting, geographical location, sensory impairment and dementia diagnosis ascertainment, follow-up years and number of adjusted covariates.Ethics and disseminationEthical approval is not required because this study involves data already published by other authors. Our findings will be disseminated by a peer-reviewed publication and presentations at relevant scientific conferences. The results will support the understanding of dementia’s modifiable risk factors and may motivate the development of screening interventions to prevent dementia.PROSPERO registration numberCRD42023493401.